Review of medical physiology - Ganong, William F. (A concise medical library for practitioner and student, 1985)
This book is designed to provide a concise summary of mammalian and, particularly, of human physiology which medical students and others can supplement with readings in current texts, monographs, and reviews. Pertinent aspects of general and comparative physiology are also included. Summaries of relevant anatomic considerations will be found in each section, but this book is written primarily for those who have some knowledge of anatomy, chemistry, and biochemistry. Examples from clinical medicine are given where pertinent to illustrate physiologic points. Physicians desiring to use this book as a review will find short discussions of important symptoms produced by disordered function in several sections.